Dielectric Property Analysis of Seafood Contaminants using Minkowski Fractal Antenna - ARLIZ, ABDUL SAMAT (CGS, UNIMAS, 2025)
Malaysia’s extensive coastline has abundant access to marine products such as fish, prawns, and other seafood. However, contamination of these marine products poses significant risks to food safety and public health, affecting both consumers and vendors. Contaminated seafood, often harboring pathogens like Salmonella and Vibrio, can lead to severe food poisoning depends on the concentration of these microbes. Mass spectrometers are high-precision instruments commonly used for detecting food contaminants. They can accurately identify and quantify various pathogens, pesticides, and toxins by analyzing the mass-to-charge ratio of ions. Despite their precision, the process from sample collection to result interpretation can take 6 to 24 hours and the high cost of these devices limits their accessibility for smaller laboratories and food producers. To address these limitations, this study explores the use of the Minkowski Fractal Antenna as a cost-effective and non-destructive alternative for food contamination detection. Several tests have been conducted to demonstrate the validity of the Minkowski Fractal Antenna as a resonator. The results shows that the designed Minkowski Fractal Antenna serves as a resonator where it can detect differences in return loss results when dispersed in solutions with seafood contaminants, offering a cheaper alternative to commercialized methods.